Are International Undergraduates Struggling Academically? - Fass-Holmes, Barry; Vaughn, Allison A. (Journal of International Students, 2014)
Are international undergraduates struggling academically, and are their struggles due to weaknesses in English as a second language? The present study showed that 1) at most 10% of these students in three cohorts (ranging in size from N=322 to N=695) at an American west coast public university struggled (quarterly grade point averages below C) in their university classes; 2) up to 63% of them struggled with English (they were required to take a local community college’s English Composition and/or English as a Second Language classes, and up to 42% earned course grades of D or F in those classes); and 3) predictors shown to be statistically significant by hierarchical linear modeling each accounted for less than 5% of the total variance (“small” effect sizes). These findings suggest that only a minority of this university’s international undergraduates struggle in their university classes even though a majority of them struggle with English.